Integration von XR-Anwendungen im physischen Store - Katja Lurie-Stoyanov; Manfred Kirchgeorg (Marketing Review St.Gallen, 2022)
Increasing competitive pressure forces brick-and-mortar stores to integrate new technologies such as 'Just Walk Out' technology. This article uses an empirical online study to analyze customers' acceptance of this technology in German retailing and identifies compatibility, performance expectancy, and privacy concerns as primary influencing factors.
Keywords: 650